What's on your mind? The role of bystander behaviors in victims' cognitions about the cause of the bullying and its solution - Laninga‐Wijnen, Lydia; Graf, Daniël; Healy, Karyn; Yanagida, Takuya; Salmivalli, Christina; Garandeau, Claire F. (Wiley, 2026)
It is commonly assumed that victims' maladaptive cognitions concerning the cause of their victimization (self-blame) or its potential solution (e.g., helplessness) contribute to psychological problems. Nevertheless, there is limited empirical research on the conditions that lead to the emergence of such cognitions. The present study investigates whether bystanders' behaviors during bullying incidents (bystanders joining the bullying or defending the victim) influence victims' attributions of the cause (self-blame) and perceived solutions (i.e., internal or external solution, or helplessness) to bullying, both concurrently and over time. A total of n = 755 victims (Mage = 12.75, SD = 1.77; 54.8% girls) from 379 classrooms in 49 schools were drawn from a larger sample of n = 6537 students participating in the SOLID project. Concurrent regression analyses indicated that victims whose bystanders joined the bullying (n = 345) experienced higher self-blame and helplessness at T1 compared with victims whose bystanders did not join the bullying (n = 364). Victims whose bystanders defended them (n = 458) experienced lower self-blame and helplessness, and a stronger belief in an internal or external solution to the bullying, compared with victims whose bystanders did not defend them (n = 286). Latent change score models indicated that over time, victims whose bystanders joined the bullying experienced less favorable change (i.e., stronger increase, weaker decrease) in self-blame over time than victims whose bystanders did not join the bullying. Defended victims slightly differed from non-defended victims in some cognitions about the solution (e.g., lower helplessness), but only if their victimization decreased between T1 and T2. Thus, bystander behaviors may shape victims' cognitions in response to bullying incidents. Anti-bullying intervention should emphasize that bystanders should not join in the bullying; further research is needed to clarify when and how bystanders' defending is helpful.